Islamic Political Ethics: An Analysis of Generation Z’s Views on the Practice of Risywah During Elections - Akkeu Iswara; Aliya Safitri Nurwan; Dini Fuji Amila; Salsa Nurul Fauziah; Uray Nikita Aisya Syakina; Zahra Nisfi Islami; Edi Suresman (Madani: Jurnal Ilmiah Multidisiplin, 2026)
General elections (Pemilu) are a crucial instrument in a democracy that adheres to a representative system. The election process must be conducted with transparency and freedom of expression. Elections should be conducted fairly and honestly, with each individual or community's political choices based on rational considerations and their conscience, not on any particular reward. However, the reality in Indonesia still shows the practice of risywah or the phenomenon of "Serangan Fajar," namely the giving of money or goods to voters before election day. This will certainly undermine democratic values and political integrity. This study aims to determine Generation Z's views on risywah practices in elections. The study used a descriptive quantitative approach with a survey method through a questionnaire to Generation Z respondents (born between 1997 and 2007). The results showed that the majority of respondents (89%) had experienced risywah practices in their environment. Nevertheless, there is a high ethical awareness, with 95% of respondents expressing both pro and con attitudes towards money politics and agreeing that the practice violates religious norms and the principle of justice. This indicates that the Generation has a critical attitude and a positive tendency toward politics, especially regarding risywah violations, despite being exposed to widespread vote buying.